Implementasi integrasi pendidikan kejuruan berbasis teknologi dan nilai islam di madrasah kejuruan : studi kasus MAKN ende - Alwi, Najwa Binti (Maliki Interdisciplinary Journal, 2026)
This study aims to examine the implementation of the integration of technology based vocational education and Islamic values at Madrasah Aliyah Kejuruan Negeri (MAKN) Ende. Technology-based vocational education integrated with Islamic values is a comprehensive educational model designed to produce graduates who not only possess technical skills relevant to the modern (technology - driven) workforce but also have strong character and moral values based on Islamic principles. This research employs a qualitative case study approach with data collection techniques including observation, interviews, and documentation. The results indicate that MAKN Ende has implemented technology-based vocational learning through two expertise programs : Visual Communication Design (DKV) and Software and Game Development (PPLG). The integration of Islamic values is carried out through the boarding system, where students are guided in character building, religious habituation, and the strengthening of ethics and manners for twenty four hours. The implementation of this integration runs effectively due to the support of an adaptive curriculum, teacher competence, and a religious school culture. However, the study also identifies several challenges, such as limited access to technology and the need for enhanced teacher expertise in information technology (IT). Overall, the integration of technology based vocational education and Islamic values at MAKN Ende successfully improves vocational competence while simultaneously strengthening student’s character.